2015
DOI: 10.1175/jhm-d-14-0231.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Hydrologic Response to Climate Change and Shrinking Glaciers in the Highly Glacierized Kunma Like River Catchment, Central Tian Shan

Abstract: Arid and semiarid lowland areas of central Asia are largely dependent on fluvial water originating from the Tian Shan. Mountain glaciers contribute significantly to runoff, particularly in summer. With global warming, the total glacier area in the Kunma Like River catchment declined by 13.2% during 1990–2007. For future water resources, it is essential to quantify the responses of hydrologic processes to both climate change and shrinking glaciers in glacierized catchments, such as the headwaters of the Tarim R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 67 publications
0
61
0
Order By: Relevance
“…In a previous study (Q. D. Zhao et al, ), an updated VIC‐CAS model was developed and successfully applied to the Aksu River Basin by coupling the glacier module with the original VIC 4.2 model. In the horizontal direction, glaciers were taken as a new land cover type for simulating the hydrological processes of glaciers.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study (Q. D. Zhao et al, ), an updated VIC‐CAS model was developed and successfully applied to the Aksu River Basin by coupling the glacier module with the original VIC 4.2 model. In the horizontal direction, glaciers were taken as a new land cover type for simulating the hydrological processes of glaciers.…”
Section: Modelmentioning
confidence: 99%
“…In the horizontal direction, glaciers were taken as a new land cover type for simulating the hydrological processes of glaciers. The glacier ablation process used the degree‐day model (Q. D. Zhao et al, ). Each single glacier was taken as one subbasin, and the subbasins were then divided into different altitude zones.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al (2013Zhao et al ( , 2015 For the Kumalike River and the Toxkan River, the runoff has increased 13.6 and 44.9 % during 1970-2007, and 94.5 and 100 % of the increases were attributed by precipitation increase.…”
Section: Vic-3l Modelmentioning
confidence: 99%
“…Zhao et al (2015) integrated a degree-day glacier melt algorithm into a macroscale hydrologic model (VIC) and indicated that annual and summer runoff would decrease by 9.3 and 10.4 %, respectively, for reductions in glacier areas of 13.2 % in the Y. Chen et al: Hydrological modeling in glacierized catchments of central Asia Kumalike River basin.…”
Section: Glacier Melt Modelingmentioning
confidence: 99%